ANALISIS PENINGKATAN KUALITAS JARINGAN WLAN PADA BANK MANDIRI AREA PALEMBANG SUDIRMAN DENGAN MENGGUNAKAN METODE PER CONNECTION QUEUE - misinem - misinem (Politeknik Bisnis Indonesia, 2022)
In line with the rapid development of the internet and information technology, especially in computer networks, at this time it has become one of the basic things in all aspects. The objectives to be achieved in this research are to be able to monitor and measure the performance of the Bank Mandiri WLAN (Wireless Local Area Network) network in the Palembang Sudirman area. Action Research / Action Research Methods Action research is a process in which each individual or group who wants to make changes to the situation certain procedures to try procedures that are expected to provide changes and when they reach the conclusion stage they can be held accountable, in carrying out these procedures the results of the research on analyzing the quality of the WLAN network at the Mandiri Sudirman area in the category are very good according to the TIPHON standard and in accordance with the Quality Of Service (QoS), and for the implementation of the PCQ method the delay value before the implementation of PCQ is 32 ms and after PCQ is 8 ms, while the average packet loss before the implementation of PCQ is 1.5% and after PCQ is 0%